The Films of Denys Arcand - Leach, Jim (Rutgers University Press, 2020)
Denys Arcand is best known outside Canada for three films that were nominated for Academy Awards for Best Foreign-Language Film: The Decline of the American Empire (1986), Jesus of Montreal (1989), and The Barbarian Invasions (2003), the last of which won the Award. Yet Arcand has been making films since the early 1960s. When he started making films, Quebec was rapidly transforming from a relatively homogeneous community, united by its Catholic faith and French language and culture, into a more fragmented modern society. The Films of Denys Arcand sheds light on how Arcand addressed the impact of these changes from the 1960s, when the long-drawn-out debate on Quebec's possible separation from the rest of Canada began, to the present, in which the traditional cultural heritage has been further fragmented by the increasing presence of diasporic communities. His career and films offer an ideal case study for exploring the contradictions and tensions that have shaped Quebec cinema and culture in a period of increasing globalization and technological change.
https://katalog.adlr.link/Record/51-9780813598864